Formation of Cotton Fiber Structure (Eurasian Research Bulletin, 2023)
The article provides information about the stages of formation of the structure of cotton fiber, biosynthesis processes, the ordered arrangement of cellulose macromolecules during the formation of the structure of cotton fiber, the effect of chemicals on the properties of cellulose.